Marital Quality in Lithuanian Families - Maslauskaitė, Aušra (Sociologija. Mintis ir veiksmas, 2005)
This article is dedicated to the exploration of marital quality in the Lithuanian families and based on the analysis of the sociological survey data (N=500). Marital quality is measured with the Marital Satisfaction (EMS) scale. The article examines the effect of marital quality on the emotional cohesion, conflict level, conflict management style, role sharing in the domestic work and attitudes toward the partnership formation patterns. Married or cohabiting women in Lithuanian society are more dissatisfied with the marital quality than men are. Gender is the strongest factor, which predicts marital quality. Testing other variables, i.e. class, age, family structure or family background proved no significant connection with the marital quality. Marital quality positively affects the emotional cohesion of partners, reduces the conflict level and leads to the symmetrical role sharing in the couple. Higher levels of satisfaction with marital life are bound with the positive attitudes toward the institutional partnership formation patterns.
Keywords: marital relations; life quality; marital satisfaction